Predictors of psychosocial adaptation and mental wellbeing among people with chronic illness and disabilities in a chinese context. (13th April 2021) - Siu, A.; Chan, S.; Cheung, M.; Mo, C.; Lai, S.; Shek, D.
Abstract : Introduction: The process of adjustment to disability and illness among people with chronic illness and disabilities (CID) impacts on motivation for rehabilitation illness self-management, and psychological well-being. It involves a complex interplay of biopsychosocial factors, and was seldom examined in the Chinese context. Objectives: Identify the predictors of mental well-being of people with from a set of variables including illness and social support, functional abilities, coping strategies, resilience. Examine how these factors interact in determining psychosocial adaptation and mental well-being by structural equations modelling (SEM). Methods: We conducted a survey of people with CID, who were recruited from community-rehabilitation settings and self-help groups (N = 244). The research questionnaire collected basic demographic information, illness-related variables (e.g. pain, fatigue, functional limitations), and RIDI), social support, measures of resilience, coping, psychosocial ad as predictors, and mental well-being. Results: Of General Linear Model (GLM) revealed that males have better adaptation than females. Resilience, social coping, & active problem solving are significant predictors of adaptation (Table 1), while age, breathing, pain, resilience, avoidance coping, are predictors of maladaptation (Table 2). A SEM was tested to examine the interaction among the predictors and outcome of adaptation and mental well-being (Figure 1), and the model fit was fair (CFI = 0.89; RMSEA = 0.09) Conclusions: The results indicated that there are gender differences in adaptation. While all the hypothesized groups of variables contributed to mental well-being of people with CID. Resilience, illness variables, and some forms of coping are closely linked to adaptation and maladaptation. Disclosure: No significant relationships.